Marginalisaing the majority: Nigerian newspaper' covergae of the rural sections in a profit-driven economy (2016)
"The study examined the performance of Nigerian print media, in the context of neoliberalism, regarding their coverage of the less-urban sections as compared to the attention given to the urban centres. The social responsibility, developmental media, and social exclusion theories provided the theoretical framework for the study. The Guardian, The Nigerian Tribune and The Vanguard—out of the national quality newspapers in Nigeria—were randomly selected for content analysis, while six reporters and two editors from the newspapers were purposively selected for in-depth interviews. Performances of the selected newspapers showed that they did not fare well in their social responsibilities and development roles. The newspapers gave more attention to the urban centres to the neglect of the rural sections while they placed monetary value on the scanty events they reported from the rural sections. The only occasions when the rural sections received appreciable media attention was when negatives stories broke. This trend negates the tenets of social responsibility and national development. All regulating agencies in the Nigerian media industry must be alive to their statutory responsibilities in order to ensure balance and fairness in the media coverage of different sections and groups in the country"